Perspectivas sobre gênero: a inserção pública da mulher no Irã do século XX - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Gender debates timidly entered the field of International Relations in the late 1980s and currently occupies an important position in the international political agenda. Throughout the years, the international relations arena has broadened its issues of interest, bringing to the multilateral forums discussions of the societal and individual levels, which go beyond the protagonism of the state as an international actor. Gender issues, inserted in the logic of expansion of international political debates, became frequent in the agenda of international and non-governmental organizations, and, consequently, more present in interstate relations. In recent years, therefore, the pressure for the development of public policies designed to increase public participation of women by states became something ordinary in the international arena. Gender issues, within the Western democratic discourse, generate constraints directly to countries that live outside the Western orbit, especially to Islamic countries, considered the largest examples of female oppression. The establishment of the Islamic Republic of Iran has placed this country in the center of Western criticism, given that in addition to following a model of government completely opposite to the Western ideal, it encouraged Iranian nationalism and made Western interests in the region more difficult to be achieved. The establishment of a theocratic government in Iran enabled the West to direct their criticism to the social relations between men and women, arguing the condition of subalternity that Islam imposed over Iranian women. The subalternity which is referenced, however, is not an exclusive characteristic of Islamic or Eastern societies, for in the West this condition is also a reality, although in different dynamics. Islam, despite to emerge as the propellant and responsible element for ensuring the unequal gender relations that are reproduced in Iran, gives way, in this research, to another element considered of greatest impact on the reification of this scenario: the social construction of Iranian civilization. Unlike the Western conception, this paper rejects the idea that the Western model of government is the way to the end the Iranian women's subordination and that Islam is the source of the marginalization of women in Iran, and considers, above any other factor, the impact of patriarchal Persian traditions in Iran's contemporary thinking to understand this situation.
Keywords: International relations; Feminism; Islam; Iran; Relações internacionais; Feminismo; Irã; Islamismo